Photocatalytic Regioselective Hydroboration of Indoles and Benzofurans with N-Heterocyclic Carbene Boranes - Pang, Yubing; Ma, Zongyang; Ye, Juntao (Synthesis, 2025)
Dearomative hydroboration of arenes using nucleophilic boryl radicals provides a powerful strategy for converting flat, abundant arenes into valuable, three-dimensional organoboron architectures. While such reactions are well established for electron-deficient arenes, the analogous transformation of electron-rich heteroarenes remains challenging due to a polarity mismatch. Herein, we report a photocatalytic approach that enables the regioselective, dearomative hydroboration of both electron-rich and electron-deficient indoles and benzofurans using N-heterocyclic carbene boranes. Density functional theory calculations indicate that the C2 addition of the boryl radical is kinetically favored over the C3 addition, and that the addition step becomes irreversible due to a subsequent, low-barrier hydrogen-atom-transfer event.
Keywords: Photocatalysis; Boryl radical; Hydroboration; Dearomatization; Organoboron; N-heterocyclic carbene borane